Antimicrobial, antibiofilm and cytotoxic effects of a colloidal nanocarrier composed by chitosan-coated iron oxide nanoparticles loaded with chlorhexidine - Araujo, Heitor Ceolin [UNESP] (2020)
Objectives: This study evaluated the antimicrobial and antibiofilm effects of a colloidal nanocarrier for chlorhexidine (CHX) on Candida glabrata and Enterococcus faecalis, as well as tested its cytotoxic effect on murine fibroblasts. Methods: Iron oxide nanoparticles (IONPs) were coated with chitosan (CS) and loaded with CHX at 31.2, 78 and 156 μg/mL. Antimicrobial effects were assessed by determining the minimum inhibitory concentration (MIC), using the broth microdilution method, and fractional inhibitory concentration index (FICI). Preformed biofilms (48 h) were treated with different concentrations of the nanocarrier (24 h) and quantified by colony-forming units (CFUs), total biomass and metabolic activity. For cytotoxicity, the viability of L929 cells was evaluated by MTT assay after 24 and 48 h of exposure to the nanocarrier. Data were submitted to ANOVA and Fisher LSD or Tukey post-hoc tests (α = 0.05). Results: MIC and FICI results showed an indifferent interaction among the components of the nanocarrier for all strains evaluated. CHX alone and nanocarrier containing 156 μg/mL CHX did not differ from each other in reducing the number of CFUs. However, the nanocarrier containing 156 μg/mL CHX promoted the highest reductions in total biofilm biomass and metabolism, surpassing the effect of CHX alone. After 24 and 48 h of exposure, the nanocarrier reduced CHX toxicity to the L929 cell at low concentrations. Conclusion: These findings suggest that the CHX nanocarrier has potential to be used in the control of oral diseases associated with C. glabrata and E. faecalis. Clinical relevance: CHX has improved the antibiofilm effect and reduced the cytotoxicity (at low concentrations) when conjugated to CS-coated IONPs. This new colloidal formulation has potential as an alternative antimicrobial agent to pure CHX for the control of biofilm-related oral diseases, such as oral candidiasis and endodontic infections.